Prevalence of Musculoskeletal Disorders among Health Sciences Student Tablet Users at Naresuan University - นามวงษา สุวลี; กิตติตระการ ธารารัตน์; โมราสุข โยษิตา; สุขวิเศษ พัณณิตา; วงษ์จีน วโรชา (Journal of Health Science of Thailand, 2024)
The purposes of this study were to explore the prevalence of musculoskeletal disorders and to compare their affected body regions among tablet-using Health Science students at Naresuan University. A questionnaire survey was conducted among 555 participants. It was found that 397 participants (71.53%) had musculoskeletal disorders after using their tablet. The highest prevalence of musculoskeletal disorders in the past 7 days and the past 12 months at the neck was 31.99% and 32.49%, respectively; upper back - both sides 17.38% and 15.87%, respectively; and lower back - both sides was 14.61% and 14.86. The second-highest prevalence was at the upper extremities group including shoulder - right side 10.33% and shoulder - both sides 11.08%; wrist and hand - right side 10.83% and 9.57%; and elbow - left side 3.53% and right side 2.27%; and the least prevalence was at the lower extremities group including hip 7.30% and 8.56% for the past 7 days and 12 months, respectively; knee 6.30% and 6.05%; and ankle and foot 4.03% and 7.05%. In conclusion, the Health Science student tablet users at Naresuan University had musculoskeletal disorders in all body regions. The most prevalent was in the spine group, especially the neck area.